Community health workers capacity in teaching skills and work-related stress: A study in Iranian health system - Zeinab Javadivala; Fatemeh Nazari; Shayesteh Shirzadi; Neda Gilani; Devender Bhalla (BioSocial Health Journal)
Introduction: This study aimed to examine the associations between teaching skills and job-related stress among the mentors of community health workers (M-CHWs). Methods: This cross-sectional study was conducted from May to December 2018 in Iran. Through census, all 110 M-CHWs from the rural health worker educational institutions (RHWEIs) were invited to participate in the study. Applying structured questionnaires, data were collected through face-to-face interviews. Results: The analysis yielded a maximum canonical correlation coefficient of .96 between teaching skills and work-related stress which was statistically significant (Wilks’s λ=.014 criterion, F (42, 317.71)=11.29, P<0.001). Results showed moderate to strong significant relationships between subscales of teaching skills and work-related stress (P<0.05). Conclusion: Our findings call attention to the relationships between teaching strategies, teaching program, and professional knowledge by total teaching skills. The M-CHWs’ well understanding of their role was correlated with less experiencing work-related stress.